2012
DOI: 10.1177/039463201202500212
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor Kinetics in Septic Shock Patients: A Preliminary Study

Abstract: The aim of this study is to evaluate some inflammatory parameter changes in septic shock patients and their possible correlation with clinical outcome, in particular when continuous veno-venous hemofiltration (CVVH) treatment is required. Considering the objective difficulty in enrolling this kind of patient, a preliminary study was initiated on seventeen septic shock patients admitted to a medical and surgical ICU. The mRNA expression of Toll-like receptor (TLR)-1, TLR-2, TLR-4, TLR-5, TLR-9, TNFα, IL-8 and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(27 reference statements)
1
3
1
Order By: Relevance
“…The LPS-induced overexpression of TLR4 is associated with changes in the levels of inflammatory mediators. Accumulating evidence has suggested that LPS-induced overactivation of the TLR4 signaling pathway leads to an increase in the production of pro-inflammatory mediators, with fatal consequences to the host (21)(22)(23). The results of the present study demonstrated that exposure to 20 mg/kg LPS increased the expression levels of TLR4 in mice colon tissue.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The LPS-induced overexpression of TLR4 is associated with changes in the levels of inflammatory mediators. Accumulating evidence has suggested that LPS-induced overactivation of the TLR4 signaling pathway leads to an increase in the production of pro-inflammatory mediators, with fatal consequences to the host (21)(22)(23). The results of the present study demonstrated that exposure to 20 mg/kg LPS increased the expression levels of TLR4 in mice colon tissue.…”
Section: Discussionsupporting
confidence: 59%
“…The TLR4 receptor detects foreign antigens and initiates the innate immune response. The ability of TLR4 to rapidly detect pathogens is key to the inflammatory response initiated in patients with severe sepsis (21). The LPS-induced overexpression of TLR4 is associated with changes in the levels of inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…In a septic-shock study, investigators found that 35% of patients had a down-regulation of TLR gene expression compared to their baseline values (32). We are of the opinion that the low levels of serum TLR9 detected in our study were because of down-regulation in these sepsis cases.…”
Section: Discussioncontrasting
confidence: 38%
“…TLR2 has been described to be crucial in joint infection (20), contributing to the degenerative process and destructive arthropathy after microbial joint infection (23), indicating that TLR2 expression strictly reflects the progression of the infection in the host. So far, the alteration of TLR2 and TLR4 has been evaluated only at the gene expression level (24,25), while the present work is the first, to our knowledge, which measures the amount of circulating protein, making it suitable for routine clinical diagnosis. In order to evaluate TLR2 circulating levels as diagnostic tools, we compared them with canonical markers of infection and inflammation.…”
mentioning
confidence: 99%